Investigation variance in human psychological responses to wooden indoor environments. (15th November 2016) - Zhang, Xi; Lian, Zhiwei; Ding, Qingfeng
Abstract: Indoor environment is of tremendous importance in people's daily life since it is where almost two-thirds of their lifetime is spent. Current studies are mainly focused on steel concrete structured buildings, whereas very few are concerned with wooden ones. How wooden buildings benefit human beings is still not clear. The purpose of this study was to investigate the different psychological responses to both wooden and non-wooden indoor environments assessed by systematic and quantitative tests. Twenty participants' psychological responses were evaluated in a sixty-minute survey including the Profile of Mood States (POMS), the fatigue symptom checklist, and a subjective evaluation. The results demonstrated that more positive emotions were generated in wooden environments than in non-wooden environments during the entire experimental process. Additionally, fatigue evaluation values of wooden environments were dramatically lower than those of non-wooden environments after continuous working, which implied that the participants in wooden environments suffered from less fatigue. Compared to non-wooden rooms, wooden ones were considered as more comfortable environments, whose occupants enjoyed a more delightful sense of color, odor, and light. Highlights: We performed a comparative study between wooden and non-wooden indoor environments. Participants have more positive emotions in wooden rooms, especially after working. Working in a non-wooden environment is more likely to produce fatigue. Wooden environment had the potential to restore the ability to regulate emotion and relieve stress. Participants feel more warmth and brightness in wooden rooms and have sensitivity to odor.